Application of Tungsten Nanopowder in Manual Metal Arc, Metal Inert Gas, and Flux-Cored Arc Welding Surfacing - Evgenii Zernin; Ekaterina Petrova; Alexander Scherbakov; Ekaterina Pozdeeva; Anatolij Blohin (Metals)
The main directions and fields of the application of metal nanopowders in joining technologies are considered. Based on this analysis, the purpose of this research was to determine the effect of tungsten nanopowder on the structure and properties of the deposited metal. In order to increase the efficiency of using tungsten nanopowder for modification, it is necessary to ensure the introduction of nanopowder into the low-temperature zone of the molten metal during surfacing. To study the metal, microstructural analysis was performed, and the microhardness of the deposited joint was determined. On the basis of the conducted studies, a change in the structure of the deposited metal and an increase in mechanical properties were revealed. A conclusion is made about the effect of tungsten nanopowder on the metal modification process during manual metal arc, metal inert gas, and flux-cored arc welding. Based on the conducted studies, it was found that the introduction of tungsten nanopowder into the low-temperature zone of the molten metal ensures the modification of the surfacing and induces an increase in the microhardness of the deposited metal. At the same time, grains of polyhedral morphology are formed at the surface, and the structure of oriented dendrites at the boundary of fusion with the base metal is also revealed, showing the peculiarities of the distribution of microhardness in various surfacing methods. The minimum and maximum values of microhardness depend not only on the nanopowder but also on the method of its introduction into the molten metal.